Limb Muscle Explosiveness and Arm Muscle Explosive Power to The Precision of The Lantern Ball Player Smash - Chan, April; Gustian, Deri; Nevilta, Ariotia (Yayasan Sekora, 2017)
The problem in this research stems from the writer's observations in the field, it turns out that the LENTERA Padang volleyball player's smash accuracy is still low. The purpose of this study was to determine the relationship between the explosive power of the leg muscles and the explosive power of the arm muscles on the accuracy of the Smash. This type of research is correlational. The population in this study were 20 male volleyball players LENTERA Padang, using a total sampling technique in which all populations were sampled. To obtain the research data, the vertical jump test, two hand medicine ball put test and accuracy of Smash were used. The data obtained were analyzed by using product moment correlation. Based on the data analysis, it was found that the results obtained by the explosive power of the leg muscles had a significant relationship with the accuracy of the smash of the LENTERA Padang volleyball player, indicated by the results obtained, namely rcount 0.72> r table 0.444, from the results obtained that the explosive power of the arm muscles had a significant relationship. with the accuracy of the LENTERA Padang volleyball player Smash accuracy, indicated by the results obtained, namely rcount 0.51> r table 0.444, there is a significant relationship jointly between the explosive power of the leg muscles and the explosive power of the arm muscles with the accuracy ability of the LENTERA Padang volleyball player Smash, This is indicated by the results obtained by Rhitung 0.73> Rtabel 0.444